Redox transformation of poly(o-aminophenol) (POAP) under continuous potential cycling - Tucceri, Ismael Ricardo (2015)
The aim of this work was to study the effect of prolonged potentiodynamic cycling (PPC) on the conducting properties of poly(oaminophenol) (POAP) film electrodes. PPC reduces strongly the electron and ion transport rates at POAP films. This effect is called here deactivation. Cyclic Voltammetry (CV), Rotating Disc Electrode Voltammetry (RDEV) and Electrochemical Impedance Spectroscopy (EIS) were employed in this study. The attenuation of the voltammetric response of the polymer with the increase in the number of oxidation-reduction cycles allowed one to define a degree of deactivation. RDEV and EIS were employed to obtain dependences of charge-transport and charge-transfer parameters on the degree of deactivation of the polymer. RDEV data were interpreted on the basis of the electron hopping model. Impedance spectra of POAP films in the presence of an electroactive solution containing p-benzoquinone (Q) and hydroquinone (HQ) species were analyzed on the basis of an impedance model which considers a uniform and nonporous polymer film and no penetration of redox species into the film from the solution While diffusion coefficients for electron (De) and ion (Di) transport decrease, interfacial resistances related to ion (Ri f s) and electron (Rm f, Ref s) transfer across the different interfaces involved in the metal/polymer film/solution system increase as the degree of deactivation increases. The slower electron transport with the increase in the degree of deactivation was attributed to the increase of the electron hopping distance between redox sites. Transport parameters, such as, Rif s and Di, were associated with proton movements. POAP films maintain their conducting properties almost unaltered for about 500 potential cycles at a scan rate of 0.010 V s-1. However, a loss of conductivity was observed as the number of potential cycles was extended beyond 500.